Pengaruh Pendidikan Kesehatan Terhadap Tingkat Pengetahuan dan Sikap Pasien Asma Bronkial Dalam Pencegahan Serangan Asma - Arvida. Bar; Selvi Narti; Mursidah Dewi; Loriza Sativa Yan (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2021)
Asthma is a respiratory disease that is often found in both children and adults. A group of patients may be free from long-term attacks of symptoms if they exercise or are exposed to allergens or viral infections of the respiratory tract. Other patients may experience persistent symptoms or frequent acute attacks. Asthma causes patients to require treatment, both in hospital and at home. This study aims to determine the effect of health education on the knowledge and attitudes of asthma patients in the prevention of recurrence in the work area of Putri Ayu Public Health Center. This research is a quantitative study with a pre-experimental design, one group pre-test and post-test. Total sample of 37 respondents The population in this study are patients with asthma problems which are the scope of the work area of Putri Ayu Public Health Center. The data collection technique used was done by using a questionnaire (question list), while the data analysis used the mc nemar test. Mcnemar statistical test results show the p-value (0.000) <0.05, meaning that there is an effect of health education on the level of knowledge of respondents in preventing asthma attacks. The results of the Mcnemar statistical test showed a p-value (0.000) < 0.05 meaning that there was an effect of health education on the level of knowledge of asthmatics in the Putri Ayu Health Center work area, Jambi City